Genetic susceptibility associated with hospitalization due to respiratory syncytial virus in a group of Taiwanese children: a preliminary study - Yi-An Lu; Chi-Jen Chen; Tzu-Pin Lu; Jin-Yuan Wang; Daniel Tsung-Ning Huang; Daniel Tsung-Ning Huang (Frontiers in Pediatrics)
BackgroundRespiratory syncytial virus (RSV) is a leading cause of lower respiratory tract infections in young children worldwide. While several risk factors for severe RSV illness are known, the role of host genetic susceptibility remains underexplored, particularly in East Asian populations. Objective: This preliminary study aimed to identify genetic variants associated with RSV-related hospitalization in the Taiwanese pediatric population using a genome-wide association approach.MethodsA total of 260 children aged ≥6 months were recruited from Mackay Memorial Hospital and the corresponding author's social media page between November 2020 and March 2022. Genotyping was performed using the Axiom Genome-Wide TPM 2.0 array, followed by imputation and quality control. Genome-wide association analyses were conducted under additive, dominant, and recessive models, adjusting for population stratification.ResultsEight single nucleotide polymorphisms (SNPs) were significantly associated with RSV hospitalization risk (rs183825, rs141541148, rs7296788, rs16862251, rs1525107, rs2105758, rs622946, and rs12857032). Notably, rs141541148 (OR = 9.14) and rs1361088 (OR = 8.58 in boys) were associated with substantially increased risk. Conversely, rs16862251 was linked to a reduced risk (OR = 0.19), suggesting a protective role possibly mediated through T-cell receptor signaling.ConclusionOur findings identify several gene loci associated with higher rates of hospital admissions due to RSV in children of ≥6 months of age. By studying the genetic variations that may predispose people to RSV infection, it may be possible to gain a better understanding of risk factors and prioritize vaccination for specific populations.